Estrategias de Marketing en El Comisariato Del Pollo de la Parroquia La Unión en el período 2023. - Sánchez Prieto, Karen Belén (2024)
Applying different marketing strategies in any company is an essential tool for it to have more recognition and relevance within the business environment, the implementation of effective strategies promotes positive business growth, for this reason the objective of this research is to analyze the marketing strategies in the chicken commissary, in which it has been shown that the prices it handles and the quality of the products it offers are of good quality, however, in the company they only use traditional marketing which is deficient, since it does not use strategies that allow it to reach a new public, generating more sales opportunities. The chicken salesman can apply new marketing strategies. Implementing different plans that include social networks, advertising through digital screens, web pages or Facebook pages, in order to have greater growth in sales and an increase in your clientele, it is currently important to have a well-defined marketing strategy, which is clear and effective, so that in this way better results can be obtained, in the same way having a safe plan helps the company to be prepared for all types of situations that may occur unexpectedly and thus be able to have positive results for the company.